Teknik Marmet terhadap Kelancaran Asi pada Ibu Post Partum - Wasis Pujiati; Lili Sartika; Liza Wati; R Alya Ramadinta (Fakultas Ilmu Kesehatan, 2021)
Breast milk is a liquid produced by mothers as the best food intake for the nutritional needs of babies. Several problems related to breastfeeding in post partum mothers are lactation management which is less effective on the first day of birth, caused by lack of knowledge and stress. One of the methods used to overcome breast milk insufficiency is the marmet technique. Marmet technique is a combination of massage that is effective, manual, safe and free of cost. The marmet technique is an optimal effort to stimulate the hormones oxytocin and prolactin in the smooth flow of breast milk. The purpose of this study was to determine the effect of the marmet technique on the smoothness of breastfeeding in post partum mothers in the Tanjungpinang City Health Center Work Area. This is a study with a quasi-experimental design (Quasi Experiment) with a Pre and Post Test without Control design. The research population was post partum mothers as many as 201 people and the number of samples was 30 respondents. Samples were taken using purposive sampling. Hypothesis test using non parametric by doing Wilcoxon test. The results showed that there was an effect of the marmet technique on the smoothness of breastfeeding in post partum mothers with a value of 0.000. Research recommendations for effective marmet techniques are carried out to launch breast milk in postpartum mothers and the marmet technique can stimulate an increase in the hormones prolaksin and oxytocin so that it has a relaxing effect on postpartum mothers